Design, Fabrication and Performance Evaluation of a Poultry Feed Pelleting Machine - Okwuchukwu Innocent Ani; Rowland Iheanyichukwu Odinma; John Ndubuisi Ani (Britain International of Exact Sciences (BIoEx) Journal, 2023)
The poultry industry plays a crucial role in meeting the global demand for animal protein. To ensure optimal growth and productivity of poultry, the formulation and processing of high-quality feed are essential. Feed pelleting is a common method employed to enhance the nutritional value, digestibility, and handling characteristics of poultry feed. The machine which meant for the production of poultry feed pellets in good quantities, was designed, fabricated and its performance evaluation was carried out accordingly. The independent dual operated Poultry Feed Pelleting Machine permits constant production line since the prime mover (diesel engine) would be plunged into operation as at when due, that is, when electricity power supply failed. The materials used were locally sourced which included; mild steel, high carbon steel, aluminum, 3hp electric motor, prime mover and axle. The base materials are corn, soybean, wheat, rice bran, wheat bran, herbs, fish meal, groundnut cake etc. The machine functioned reliably at the throughput capacity of 95kg per hour and up to 800kg per day with 95% efficiency proved its high performing rate. Moreover, the study showed that useful information in designing pelleting machine that produced pellet optimally when the appropriate moisture condition for feed materials is considered ranging from 20% - 30% with temperature range of 500C-700C. The results indicate that the developed machine offers significant advantages in terms of pellet quality, production efficiency, and energy consumption compared to conventional pelleting methods. The developed machine is recommended to facilitate the production of poultry feed pellets for small scale and medium scale farmers.